Genetically modified crops in Africa: Economic and policy lessons from countries south of the Sahara - Falck-Zepeda, José B.; Gruère, Guillaume P.; Sithole-Niang, Idah (International Food Policy Research Institute, 2013)
The agricultural productivity challenges facing Africa will require a proactive response and vigilant evaluation of biotechnology and its many tools. Genetically Modified Crops in Africa is meant to help policymakers assess whether and how biotechnology can contribute sustainable solutions to ending hunger and poverty in Africa.